2014
DOI: 10.1037/a0035963
|View full text |Cite
|
Sign up to set email alerts
|

A time to remember: The role of circadian clocks in learning and memory.

Abstract: The circadian system has pronounced influence on learning and memory, manifesting as marked changes in memory acquisition and recall across the day. From a mechanistic level, the majority of studies have investigated mammalian hippocampal dependent learning and memory, as this system is highly tractable. The hippocampus plays a major role in learning and memory and has the potential to integrate circadian information in many ways, including information from local, independent oscillators, and through circadian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
131
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(136 citation statements)
references
References 253 publications
(435 reference statements)
3
131
0
1
Order By: Relevance
“…The circadian system can also influence the acquisition and recall of learned behaviors (Chaudhury and Colwell, 2002;Eckel-Mahan et al, 2008;Fernandez et al, 2003;Lyons et al, 2006) both in rodents (Chaudhury and Colwell, 2002;Hauber and Bareiss, 2001;Lyons et al, 2005) and humans, in which time of day influences memory (Maury and Queinnec, 1992;Nesca and Koulack, 1994). These observations suggest a fundamental interaction between the functions and processing of the hippocampus and the circadian system (Hauber and Bareiss, 2001;Martin-Fairey and Nunez, 2014;Nesca and Koulack, 1994;Smarr et al, 2014).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…The circadian system can also influence the acquisition and recall of learned behaviors (Chaudhury and Colwell, 2002;Eckel-Mahan et al, 2008;Fernandez et al, 2003;Lyons et al, 2006) both in rodents (Chaudhury and Colwell, 2002;Hauber and Bareiss, 2001;Lyons et al, 2005) and humans, in which time of day influences memory (Maury and Queinnec, 1992;Nesca and Koulack, 1994). These observations suggest a fundamental interaction between the functions and processing of the hippocampus and the circadian system (Hauber and Bareiss, 2001;Martin-Fairey and Nunez, 2014;Nesca and Koulack, 1994;Smarr et al, 2014).…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, it may participate in a variety of autonomic, neuroendocrine, defensive, ingestion-related and reproductive control systems (Bannerman et al, 2004;Kjelstrup et al, 2008). Many of these features are interlinked and are responsive to environmental changes (Hauber and Bareiss, 2001;MartinFairey and Nunez, 2014;Smarr et al, 2014). The light/dark cycle is the most striking of the environmental variations that are able to exert a potent synchronizer role in the biological rhythms (Moore-Ede et al, 1982;Mrosovsky and Salmon, 1987;Rea, 1998).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…24,25 Prior studies showed that circadian desynchrony disrupts learning and memory. 26 Circadian disruption through constant light exposure impairs hippocampus-dependent memory. 27,28 In Siberian hamsters, a one-time photic treatment that results in circadian arrhythmicity impairs novel-object recognition.…”
Section: Discussionmentioning
confidence: 99%